Genetic changes in the genus Vitis and the domestication of vine - Guzmán-Ardiles, Ruth Elena; Pegoraro, Camila; da Maia, Luciano Carlos; Costa de Oliveira, Antônio (Frontiers in Plant Science, 2023)
The genus Vitis belongs to the Vitaceae family and is divided into two subgenera: Muscadinia and Vitis, the main difference between these subgenera being the number of chromosomes. There are many hypotheses about the origin of the genus, which have been formed with archaeological studies and lately with molecular analyses. Even though there is no consensus on the place of origin, these studies have shown that grapes have been used by man since ancient times, starting later on its domestication. Most studies point to the Near East and Greece as the beginning of domestication, current research suggests it took place in parallel in different sites, but in all cases Vitis vinifera sylvestris seems to be the species chosen by our ancestors to give rise to the now known V. vinifera vinifera. Its evolution and expansion into other territories followed the formation of new empires and their expansion, and this is where the historical importance of this crop lies. In this process, plants with hermaphrodite flowers were preferentially selected, with firmer, sweeter, larger fruits of different colors, thus favoring the selection of genes associated with these traits, also resulting in a change in seed morphology. Currently, genetic improvement programs have made use of wild species for the introgression of disease resistance genes and tolerance to diverse soil and climate environments. In addition, the mapping of genes of interest, both linked to agronomic and fruit quality traits, has allowed the use of molecular markers for assisted selection. Information on the domestication process and genetic resources help to understand the gene pool available for the development of cultivars that respond to producer and consumer requirements.